The textual thresholds in the novel Tuk Jasmine by the lame Wassini AL aeraj - AL Pitar, Yaaqob; AL Abdo, Zakoan; Al_ Shekh Hossein, Hameeda (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The thresholds were not of interest in criticism before the concept of text was expanded. The concept of text did not expand until after the awareness and progress in identifying its various parts and details had been crystallized. This led to the crystallization of the concept of textual interaction. Has become an important space in modern critical thought. This development of text comprehension and textual interaction was more appropriate to achieve the view of text, as space, and then came to pay attention to its thresholds. The text can not provide naked texts that distort it, because its value is determined not only by its content and itself, but also by the various texts it forms. Contemporary criticism today sought to take care of the so-called "text entries" or "thresholds of text" That until recently was left to the marginalized aspects of criticism. This attention is due to the importance of these entries in the reading of the text, and the disclosure of its status and aesthetic significance, these thresholds are signs have many functions in the creation of emotional desires of the recipient push him to break into the text.